Shared Heritage; A Balinese Gift in A Dutch Museum - Westerlaken, Rodney (an1mage, 2018)
Indonesia and The Netherlands share heritage. Collections of Dutch museums consist of looted items, specifically the Lombok treasure and the collections gathered after the puputan Badung and Klungkung. Those collections are officially marked as war booty. Other parts of the collections are gifts towards the colonial ruler, a token of appreciation and respect. Dewa Gede Raka, the King of Gianyar, requested his Kingdom to become a protectorate of the Dutch. He was installed as stedehouder in 1900 and with that cooperated close with the Dutch. He gave a gift to the Governor General, Resident and Controleur of the Dutch Indies. Parts of this gift are nowadays in Museum Nasional, and parts are in Museum Volkenkunde. A perfect example of shared heritage. This article zooms in on the historical context of this collection (RV1436) in Museum Volkenkunde, Leiden, The Netherlands.